2019
DOI: 10.23917/jisel.v2i2.8679
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Effect Of ZIS (Zakat, Infaq, And Shadaqah), Regional Domestic Products Of Bruto, Regional Minimum Wage And Inflation On Levels Poverty In Indonesia 2012 – 2016

Abstract: This study investigated the impact of ZIS (Zakat, Infaq, and Sadaqah) Gross Regional Domestic Products, Regional Minimum Wages, and Inflation on Poverty Levels in Indonesia during the 2012-2016 period. .This paper used secondary data in the panel data form. This research conducted a quantitative approach using panel data regression. Based on the results of the panel data testing, the best model chosen is the Random Effect Model (REM). Variables of gross regional domestic products and regional minimum wages hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Malik et al (1994) examined the role of infaq in poverty alleviation in Pakistan by using zakah data and discovered that the role was just small. Mustika et al (2019) also found that the impact of infaq did not influence the level of poverty in Indonesia. In different findings, at the narrower scope, Saputro and Sidiq (2020) revealed the positive effect of infaq on economic growth, health, and human development index at Acheh province, Indonesia.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Malik et al (1994) examined the role of infaq in poverty alleviation in Pakistan by using zakah data and discovered that the role was just small. Mustika et al (2019) also found that the impact of infaq did not influence the level of poverty in Indonesia. In different findings, at the narrower scope, Saputro and Sidiq (2020) revealed the positive effect of infaq on economic growth, health, and human development index at Acheh province, Indonesia.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Selain itu didukung oleh penelitian Hanafi (2020), juga terdapat pengaruh signifikan ke arah negatif dari variabel UMK pada tingkat kemiskinan di Kawasan Wanarkuti Banglor. Penelitian oleh Mustika et al (2019) juga memaparkan bahwa tingkat kemiskinan di Indonesia juga dipengaruhi secara signifikan oleh variabel Upah Minimum.…”
Section: Pendahuluanunclassified
“…Islamic principles include the value of justice and shared prosperity so that wealth is not controlled by a certain few people (Farook & Farooq, 2013). Zakat, infaq and sadaqah (ZIS) in a modern economy can provide a role inequitable welfare distribution to reduce social inequality in society (Mustika et al, 2019;Purwanti, 2020). ZIS is one element that can positively affect economic growth and financial literacy, so the mechanism and acceleration of paying ZIS must be improved (Rizal et al, 2020;Wahab & Rahman, 2011).…”
Section: Introductionmentioning
confidence: 99%